The relationship between nectaries and floral architecture: a case study in Geraniaceae and Hypseocharitaceae. (14th September 2017) - Jeiter, Julius; Hilger, Hartmut H; Smets, Erik F; Weigend, Maximilian
Abstract: Background and Aims: Flowers of Geraniaceae and Hypseocharitaceae are generally considered as morphologically simple. However, previous studies indicated complex diversity in floral architecture including tendencies towards synorganization. Most of the species have nectar-rewarding flowers which makes the nectaries a key component of floral organization and architecture. Here, the development of the floral nectaries is studied and placed into the context of floral architecture. Methods: Seven species from Geraniaceae and one from Hypseocharitaceae were investigated using scanning electron microscopy and light microscopy. Samples were prepared and processed using standard protocols. Key Results: The development of the nectary glands follows the same trajectory in all species studied. Minor differences occur in the onset of nectarostomata development. The most striking finding is the discovery that a short anthophore develops via intercalary growth at the level of the nectary glands. This anthophore lifts up the entire flower apart from the nectary gland itself and thus plays an important role in floral architecture, especially in the flowers of Pelargonium . Here, the zygomorphic flowers show a particularly extensive receptacular growth, resulting in the formation of a spur-like receptacular cavity ('inner spur'). The nectary gland is hidden at the base of the cavity. Various forms of compartmentalization, culminating in the 'revolver flower' of Geranium maderense, are described. Conclusions: Despite the superficial similarity of the flowers in Geraniaceae and Hypseocharitaceae, there is broad diversity in floral organization and floral architecture. While the receptacular origin of the spur-like cavity in Pelargonium had already been described, anthophore formation via intercalary growth of the receptacle in the other genera had not been previously documented. In the context of the most recent phylogenies of the families, an evolutionary series for the floral architecture is proposed, underscoring the importance of synorganization in these seemingly simple flowers.